Identifikasi bidang gelincir menggunakan metode geolistrik tahanan jenis konfigurasi Schlumberger di Bukit Lantiak Kecamatan Padang Selatan (The identification of the slip surface using the geoelectric resistivity method of the Schlumberger configuration in Bukit Lantiak, Padang Selatan District) - Irepia Refa Dona; - Akmam; Nofi Yendri Sudiar (Department of Physics – Universitas Negeri Padang UNP, 2015)
The identification of slip surface in Bukit Lantiak Padang Selatan has been done. The aim of this research is to know the shape of slip surface, depth of slip surface, and angle of slip surface. Data were collected by Automatic Resistivity Multielectrode in 4 lines with Schlumberger configuration. Interpreted of data was done with Robust Constraint Inversion. The result of this research shows that slip surface is Translation slip. Depth of slip surface are 12,8 m and 4,5 m. Angles of slip surface are 34,980 and 25,940.